2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of manual steering and steering via joystick of a flexible rhino endoscope

Abstract: Flexible endoscopes are used in ENT surgery for examination tasks in cases wherever rigid endoscopes are unsuitable to reach certain positions in the nasal cavity. Until today they are steered by hand and no robotized system has been put into clinical practice. One qualification a robot manipulator system has to fulfill to be accepted is not to create new disadvantages compared to the conventional method in surgery. An important factor is the time needed to steer the new system compared to the time needed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, according to the research results of Allemann et al. and Eckl et al., the joystick has fewer advantages than manual operation, and the operation time is longer when controlling the endoscope robots 12,13 . It is advantageous to use a joystick when the endoscope is used for diagnostic purposes such as the observation of affected areas and conducting biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the research results of Allemann et al. and Eckl et al., the joystick has fewer advantages than manual operation, and the operation time is longer when controlling the endoscope robots 12,13 . It is advantageous to use a joystick when the endoscope is used for diagnostic purposes such as the observation of affected areas and conducting biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that remote actuation platforms could not yet compete with the efficiency of conventional endoscope control [38,62,71]. The setup of these platforms prevented adequate scope manipulation [62,72,73]. This study shows that our setup and interface enable at least as efficient manipulation of the endoscope and effective visualization of the bowel wall.…”
Section: Discussionmentioning
confidence: 76%
“…Despite intuitive and ergonomic shortcomings of the conventional endoscope, experts are competent in scope manipulation without causing excessive patient pain [13,42]. Previous studies showed that remote actuation platforms could not yet compete with the efficiency of conventional endoscope control [38,62,71]. The setup of these platforms prevented adequate scope manipulation [62,72,73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations